1999
DOI: 10.4269/ajtmh.1999.61.530
|View full text |Cite
|
Sign up to set email alerts
|

Is the domestic dog (Canis familiaris) a reservoir host of American cutaneous leishmaniasis? A critical review of the current evidence.

Abstract: Abstract. Originally associated with forested areas, the transmission cycle of American cutaneous leishmaniasis (ACL) has now adapted to the domestic environment in at least 9 Latin American countries. Several studies have suggested that the domestic dog (Canis familiaris), which is already incriminated as the primary reservoir host of zoonotic visceral leishmaniasis (ZVL), may have a reservoir role in the domestic transmission of human ACL caused by Leishmania braziliensis, L. panamensis, and L. peruviana. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
110
1
21

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(134 citation statements)
references
References 123 publications
2
110
1
21
Order By: Relevance
“…Apesar de ser uma zoonose originalmente silvestre, a LTA causada pela Leishmania (Viannia) braziliensis tem sido descrita por diversos autores ocorrendo em ambientes domésticos, tendo sido aventada a possibilidade de que animais domésticos e peridomésticos, e em especial o cão, estariam funcionando como importantes fontes de infecção nesse locais 2 8 13 . Vários questionamentos ainda permanecem quanto ao verdadeiro papel do cão nessa nova adaptação do ciclo de transmissão 16 .Pouco também se conhece sobre os aspectos clínicos, parasitológicos e imunológicos do curso da infecção pela L. braziliensis em cães, sendo portanto, necessários mais estudos visando elucidar esses aspectos, que contribuirão não só para o diagnóstico precoce dos casos caninos bem como para o esclarecimento do papel dessa espécie animal na epidemiologia da LTA.O presente trabalho teve como objetivo estudar casos de cães com lesão sugestiva de LTA provenientes do Município de Maricá (Rio de Janeiro), descrevendose a apresentação das lesões e correlacionando-as com os resultados parasitológicos e sorológicos. …”
unclassified
See 2 more Smart Citations
“…Apesar de ser uma zoonose originalmente silvestre, a LTA causada pela Leishmania (Viannia) braziliensis tem sido descrita por diversos autores ocorrendo em ambientes domésticos, tendo sido aventada a possibilidade de que animais domésticos e peridomésticos, e em especial o cão, estariam funcionando como importantes fontes de infecção nesse locais 2 8 13 . Vários questionamentos ainda permanecem quanto ao verdadeiro papel do cão nessa nova adaptação do ciclo de transmissão 16 .Pouco também se conhece sobre os aspectos clínicos, parasitológicos e imunológicos do curso da infecção pela L. braziliensis em cães, sendo portanto, necessários mais estudos visando elucidar esses aspectos, que contribuirão não só para o diagnóstico precoce dos casos caninos bem como para o esclarecimento do papel dessa espécie animal na epidemiologia da LTA.O presente trabalho teve como objetivo estudar casos de cães com lesão sugestiva de LTA provenientes do Município de Maricá (Rio de Janeiro), descrevendose a apresentação das lesões e correlacionando-as com os resultados parasitológicos e sorológicos. …”
unclassified
“…Apesar de ser uma zoonose originalmente silvestre, a LTA causada pela Leishmania (Viannia) braziliensis tem sido descrita por diversos autores ocorrendo em ambientes domésticos, tendo sido aventada a possibilidade de que animais domésticos e peridomésticos, e em especial o cão, estariam funcionando como importantes fontes de infecção nesse locais 2 8 13 . Vários questionamentos ainda permanecem quanto ao verdadeiro papel do cão nessa nova adaptação do ciclo de transmissão 16 .…”
unclassified
See 1 more Smart Citation
“…The parasite has different life forms in the human host and in sand fly vectors, i.e., amastigotes, which are small and oval and promastigotes, which are longer flagellated forms of the parasite. Domestic dogs are also infected by Leishmania parasites and these animals are a reservoir for human leishmaniasis (44).…”
Section: Cutaneous Leishmaniasismentioning
confidence: 99%
“…There is no doubt that dogs play an essential role in the peridomestic transmission of visceral leishmaniasis (10), yet only risk factor analyses and isolation of Leishmania from lesions have suggested that they could play a role in American cutaneous leishmaniasis (1,7,11), and consequently confirmatory studies are still pending. We report on two cases of canine leishmaniasis in adult male, mongrel dogs residing in different endemic areas of cutaneous leishmaniasis in the Colombian Pacific coast.…”
mentioning
confidence: 99%